2020
DOI: 10.1364/oe.382608
|View full text |Cite
|
Sign up to set email alerts
|

Direct 2D spatial-coherence determination using the Fourier-analysis method: multi-parameter characterization of the P04 beamline at PETRA III

Abstract: We present a systematic 2D spatial-coherence analysis of the soft-X-ray beamline P04 at PETRA III for various beamline configurations. The influence of two different beam-defining apertures on the spatial coherence properties of the beam is discussed and optimal conditions for coherence-based experiments are found. A significant degradation of the spatial coherence in the vertical direction has been measured and sources of this degradation are identified and discussed. The Fourier-analysis method, which gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…This result is in very good agreement with a beamvibration analysis performed using a beam-diagnostic tool specifically designed to map out the full photon-beam caustic. The beam-vibration analysis using this tool revealed vertical beam-vibration amplitudes of around 125 nm in the horizontal and 500 nm in the vertical directions [10]. From simulated SAXS experiments using the disordered nanodots, we found that vibrations of 680 nm do not have any effect on the extracted spatial-coherence properties using the Fourier-analysis method.…”
Section: Lettermentioning
confidence: 88%
See 2 more Smart Citations
“…This result is in very good agreement with a beamvibration analysis performed using a beam-diagnostic tool specifically designed to map out the full photon-beam caustic. The beam-vibration analysis using this tool revealed vertical beam-vibration amplitudes of around 125 nm in the horizontal and 500 nm in the vertical directions [10]. From simulated SAXS experiments using the disordered nanodots, we found that vibrations of 680 nm do not have any effect on the extracted spatial-coherence properties using the Fourier-analysis method.…”
Section: Lettermentioning
confidence: 88%
“…Using the obtained transverse coherence lengths in horizontal and vertical directions l s,x = (1.18 ± 0.04) µm and l s,y = (5.95 ± 0.53) µm, respectively, global degrees of coherence of ζ x = (13 ± 1)% and ζ y = (50 ± 3)% are determined. This results in a total degree of coherence of ζ t = ζ x ζ y = (6.5 ± 2)%, which reflects mainly the large horizontal source size of PETRA III when using the full beam [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum spot size of the beamline (using smaller exit-slit openings than 30 μm) has been measured as 10 × 10 μm 2 ( h × v ) in the nominal focus position of the optics. 44,45 For our experiment, due to spatial constraints, the interaction region had to be placed approximately 220 mm downstream of that position; the vertical focus however was shifted accordingly using a pair of Kirkpatrick–Baez mirrors. 43 We correspondingly estimate the beam spot size at the point of interaction to be 180 × 35 μm 2 ( h × v ).…”
Section: Methodsmentioning
confidence: 99%
“…5(a) shows a series of speckle patterns from a static sample. The sample was a spatially disordered nanodot array made from a homogeneous metallic multilayer (Co 1.65 nm /Pt 2 nm ) 2 fabricated by nanosphere lithography (Bagschik et al, 2020). In the experiment, a series of 1000 patterns was taken with an exposure time of Át min = 0.12 s per pattern.…”
Section: X-ray Photon Correlation Spectroscopymentioning
confidence: 99%